Fabrication and Voltammetric Characters of Carbon Paste Electrode Modified Using Poly-Silk Peptide (Journal of Fiber Bioengineering and Informatics, 2013)
A new material poly-silk peptide was fabricated using the electropolymerization of Silk Peptide (SP) onthe surface of a Carbon Paste Electrode (CPE) for the first time. The morphological feature of poly-silkpeptide film was characterized by Scanning Electron Microscopy (SEM). The preparation conditionssuch as SP concentration, supporting electrolyte pH and scan cycles were optimized. A stable poly-silk peptide film could be obtained with scanning 16 cycles in pH7.4 Phosphate Buffer Solution (PBS)containing 0.6 g⋅L^{-1} SP between -0.5 and +1.5V. In addition, a well-defined pair of oxidative andreductive peaks of poly-silk peptide was observed in 0.1M H_2SO_4 solution (pH 1.1), resulting from thesuccessive redox reaction of -OH, -C=O and -COOH groups on poly-silk peptide.
Keywords: Silk Peptide; Electropolymerization; Carbon Paste Electrode